ЗАКОНОДАВЧІ РЕФЕРЕНДУМИ І ЗАКОНОДАВЧА РЕФЕРЕНДНА ДЕМОКРАТІЯ: ТЕОРЕТИКО-МЕТОДОЛОГІЧНІ ТА НОРМОПРОЕКТНІ АСПЕКТИ - Onischuk, M.V. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2009)
The article deals with urgent problems of the theory and practice of the legislative referenda and the corresponding forms of the referendum democracy. The essence, content and juridical attributes of the category “legislative referendum democracy” are analysed. The article also investigates a foreign experience in the legislative referendum democracy and its future consolidation trends in Ukraine.